Effect of composition of medicinal plants on growth performance, gut bacteria, hematological parameters, anticoccidial index, and optimum anticoccidial activity in domestic chicken - Habibi, Hassan; Ghahtan, Najmeh; Tohidi, Sattar; Zarrinfar, Abolfazl (Comparative clinical pathology, 2022)
In the interests of food safety and public health, plants and their compounds are now reemerging as an alternate approach to treat gastrointestinal diseases in chickens. In this study, we evaluated the impact of two edible multi-plant extract compounds on growth performance, gut bacteria, and hematological parameters, anticoccidial index (ACI), and optimum anticoccidial activity (OAA) in 17-day-old domestic chickens experimentally infected with protozoan Eimeria . The highest weight gain was recorded in the uninfected unmedicated group followed by a mixture of medicinal plants 0.01 (T 3 ) group. The basophil and total red blood cells were significantly higher in control groups in comparison with those in all other groups, and the total white blood cells were significantly lower in control groups compared with those in all other groups. Higher oocyst per gram (OPG) was recorded in the infected unmedicated group (T 2 ), followed by Karela 0.01 (T 5 ), and lower OPG in the mixture of medicinal plants 0.01 (T 3 ), T 3 , and Karela 0.001 (T 6 ), followed by sulfaclozine treatment (T 7 ). T 3 had ACI values of 129.79. According to the OAA index, the T 3 , T 4 , and T 5 groups were partially resistant and sensitive to T 6 . T 7 groups were sensitive to sulfaclozine. In this study, we found that the levels of Lactobacillus , which are positively associated with gut health, increased, whereas Clostridium , Salmonella , and total declined over time in response to the mixture of medicinal plants and Karela. These results indicated that the mixture of medicinal plants and Karela can be effectively used for the treatment of coccidiosis in domestic chickens.